2018
DOI: 10.3762/bjnano.9.258
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biological effects of spherical noble metal nanoparticles (Rh, Pd, Ag, Pt, Au) with 4–8 nm diameter

Abstract: For a comparative cytotoxicity study, nanoparticles of the noble metals Rh, Pd, Ag, Pt, and Au (spherical, average diameter 4 to 8 nm) were prepared by reduction in water and colloidally stabilized with poly(N-vinyl pyrrolidone) (PVP). Thus, their shape, size, and surface functionalization were all the same. Size and morphology of the nanoparticles were determined by dynamic light scattering (DLS), analytical disc centrifugation (differential centrifugal sedimentation, DCS), and high-resolution transmission el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 101 publications
1
18
0
Order By: Relevance
“…[ 1b,60 ] In contrast, the other noble metals form nanoparticles which are much less cytotoxic and often have small biological effects, if at all. [ 61 ] In silver‐alloyed nanoparticles, the release of silver can lead to a tunable cytotoxicity, but experience has shown that it is difficult to predict the exact level of cytotoxicity. [ 39f,60a,62 ] The presence of platinum in alloyed silver–platinum nanoparticles causes an osteopromotive activity in contact with human mesenchymal stem cells.…”
Section: Biological Properties Of Bimetallic Nanoparticlesmentioning
confidence: 99%
“…[ 1b,60 ] In contrast, the other noble metals form nanoparticles which are much less cytotoxic and often have small biological effects, if at all. [ 61 ] In silver‐alloyed nanoparticles, the release of silver can lead to a tunable cytotoxicity, but experience has shown that it is difficult to predict the exact level of cytotoxicity. [ 39f,60a,62 ] The presence of platinum in alloyed silver–platinum nanoparticles causes an osteopromotive activity in contact with human mesenchymal stem cells.…”
Section: Biological Properties Of Bimetallic Nanoparticlesmentioning
confidence: 99%
“…Reports in the literature range from no signicant adverse effects to DNA platination, genotoxicity, cell cycle arrest and an antimicrobial activity against Gram-positive bacteria. [23][24][25][26][27][28] Here, differences in shape, size and surface coating have to be taken into account, as it is now generally accepted for the assessment of the biological activity of nanoparticles. [29][30][31][32][33][34][35][36] Silver is a well-known antimicrobial agent against a broad range of bacteria, viruses, and fungi.…”
Section: Introductionmentioning
confidence: 99%
“…The gold and palladium seeds were further analysed by highresolution electron microscopy (HAADF-STEM), showing spherical polycrystalline nanoparticles (see ref. 40 for corresponding images). Both types of core-shell nanoparticles had an almost spherical shape with a diameter in good agreement with the DLS and DCS results.…”
Section: Resultsmentioning
confidence: 99%
“…44 As expected for the outer layer of palladium metal, palladium seeds and Au-Pd core-shell nanoparticles showed no distinct absorption in the visible range. 40 Clearly, palladium prevented the SPR of gold, conrming a dense layer of palladium metal around the gold core. Aer the addition of a gold layer to the surface of the palladium seeds to form Pd-Au core-shell nanoparticles, the SPR absorption band of gold was observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation